2017
DOI: 10.1038/mp.2017.242
|View full text |Cite
|
Sign up to set email alerts
|

Why is there selective subcortical vulnerability in ADHD? Clues from postmortem brain gene expression data

Abstract: Sub-cortical volumetric differences were associated with attention-deficit/hyperactivity disorder (ADHD) in a recent multi-site, mega-analysis of 1713 ADHD persons and 1529 controls. As there was a wide range of effect sizes among the sub-cortical volumes, it is possible that selective neuronal vulnerability has a role in these volumetric losses. To address this possibility, we used data from Allen Brain Atlas to investigate variability in gene expression profiles between subcortical regions of typically devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 56 publications
4
30
0
Order By: Relevance
“…In the lower left region of Figure 3 Our prior studies of SBRV in ADHD implicated the regulation of genes in apoptosis, autophagy and neurodevelopment pathways in ADHD (21,22). Neurodevelopmental pathways had also been implicated in the cross-disorder analysis of the Psychiatric Genomics Consortium (3), which suggests that cross-disorder similarities in these pathways may account for cross disorder similarities in SBRV.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the lower left region of Figure 3 Our prior studies of SBRV in ADHD implicated the regulation of genes in apoptosis, autophagy and neurodevelopment pathways in ADHD (21,22). Neurodevelopmental pathways had also been implicated in the cross-disorder analysis of the Psychiatric Genomics Consortium (3), which suggests that cross-disorder similarities in these pathways may account for cross disorder similarities in SBRV.…”
Section: Discussionmentioning
confidence: 93%
“…ENIGMA has also reported significant case vs. control differences in sMRI phenotypes for: attention-deficit/hyperactivity disorder (ADHD) (9,10), autism spectrum disorder (ASD) (11), bipolar disorder (BD) (12,13), common epilepsy syndromes (14), major depressive disorder (MDD) (15,16), obsessive compulsive disorder (OCD) (17,18) and schizophrenia (SCZ) (19,20). Each of these disorders shows a pattern of what we have termed selective brain region vulnerability (SBRV) (21,22). By this, we mean that some brain regions may be more vulnerable to the genetic and environmental risk factors associated with each disorder.…”
Section: Introductionmentioning
confidence: 99%
“…These findings challenge the idea that the core of ADHD's pathophysiology rests within the machinery of catecholaminergic transmission. Instead, it is possible that the catecholaminergic dysregulation believed to underlie ADHD is a secondary compensation to ADHD's primary etiology (see discussion by Hess et al [151]). …”
Section: Discussionmentioning
confidence: 99%
“…The latest version of the Gene Ontology (GO) database was downloaded via R package GO.db (version 3.7.0) (8) to retrieve the most up-to-date annotations for the following gene sets of interest that had previously been implicated in ADHD and that we hypothesized might be involved in SBRV: apoptosis, autophagy, neurotransmission, neurodevelopment, and reactive oxygen species (912). A total of 1,313 unique HGNC genes were identified including 43 ADHD candidate genes designated in our previous study (7). 1,288 of these had expression data in the Allen Brain Atlas.…”
Section: Methodsmentioning
confidence: 99%
“…We postulate that mechanisms underlying SBRV explain why some brain regions show structural brain changes associated with ADHD while others do not (2, 6). Previously, we found that autophagy, apoptosis, and oxidative stress pathways were associated with smaller sub-cortical brain region volumes in ADHD and suggested that they may mediate SBRV (7). The present work builds on our previous study by including newly released data from the ENIGMA-ADHD working group for cortical brain regions.…”
Section: Introductionmentioning
confidence: 93%